Ancient medicine - Langley, Andrew (Chicago, IL Raintree, 2013)
Looks at ancient medicine and explains why humans faced new challenges when they began to live together in large communities
A gift from book Africa
Science
1 2 13 15
Keywords: Medicine -- History; Medicine, Ancient; Medicine